PERLINDUNGAN HUKUM ATAS HAK PASIEN SEBAGAI KONSUMEN DALAM PELAYANAN KESEHATAN OLEH TENAGA MEDIS DI RUMAH SAKIT - Amalia, Nur Bayti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Legal protection in health services is carried out by medical personnel, namely everyone who devotes themselves to the health sector and has a professional attitude, knowledge, and skills through medical or dental professional education that requires authority to carry out health efforts in accordance with applicable regulations. This study aims to analyze the regulation and policy of legal protection of patient rights in health services by medical personnel in hospitals. The research method used is normative juridical, this method aims to understand, interpret, and explain the applicable legal system. The relationship between medical personnel and patients is a medical, interpersonal, social, economic, ethical, and legal relationship that as a whole has the potential to cause tensions between the two parties.Keywords: Legal Protection, Health Services, Medical Personnel.